Total serum bilirubin levels as mediators of antiatherosclerosis mechanisms with consideration of smoking status - Shigemasa Tani; Kazuhiro Imatake; Yasuyuki Suzuki; Tsukasa Yagi; Atsuhiko Takahashi (Tobacco Induced Diseases)
Introduction Cigarette smoking is a significant risk factor for atherosclerotic cardiovascular diseases (ASCVDs). Mildly elevated total serum bilirubin (TSB) levels can exert anti-atherosclerotic effects and may regulate inflammation. We explore the relationship between TSB levels, smoking, and inflammation.